Country Partnership Framework for the Republic of Cote d'Ivoire for the Period FY16-FY19 - World Bank Group (World Bank, Washington, DC, 2015)
This Country Partnership Framework (CPF) presents the World Bank Group (WBG) program for Côte d’Ivoire (CIV) during the period FY16-FY19. The CPF comes at an opportune moment to accelerate and scale up the WBG engagement. The program will take advantage of CIV’s current climate of renewed stability to modernize the economy and eliminate long-standing disparities aggravated by a decade of multifaceted crisis, during which the World Bank Group had to suspend its operation four times. In 2009, a transitional Government resulting from the Ouagadougou Political Agreement (OPA) provided an appropriate platform to reengage. The transitional Government prepared the country’s first Poverty Reduction Strategy Paper (PRSP) covering 2009-2015. The WBG Country Partnership Strategy (CPS) for FY10-14, which supported the PRSP’s goals, was prepared in this context. Political unrest following the 2010 Presidential Elections then rendered implementation of the 2009 PRSP difficult. During the past four years, CIV has made an impressive transition from crisis to relative stability, and from fragility and low equilibrium, through stabilization, to aspiring emerging economy status. Although some of the root causes of the conflict remain, there are high expectations that those will be tackled if the current transformation is maintained and the reconciliation agenda is intensified. The Government expects to accelerate implementation of measures designed to improve social cohesion, develop human capital, build a resilient economy, support territorial development and promote regional synergies towards integration. The CPF will also support the achievement of the WBG’s twin goals of reducing extreme poverty and boosting shared prosperity, which is also in line with Côte d’Ivoire’s plans.